Electrophysiological analysis of the epithelial H+/oligopeptide transporter, PepT1 - Beattie, L; Lorraine A. Beattie (2001)
﻿ The characteristics of transport by the epithelial, proton-coupled oligopeptide transporter, PepT1, have been investigated in PepT1 expressing Xenopus laevis oocytes using electrophysiological techniques. Membrane depolarisations and inward currents have been measured in response to various dipeptide substrates, including structurally modified and charged peptides. The latter part of this study has focussed on the role of phorbol esters on the regulation of PepT1-mediated peptide transport. I have shown that transport of neutral peptides is dependent on both pH and membrane potential. In addition, the carboxyl terminus plays an important role in substrate recognition and binding, as when blocked, the affinity of the substrate is reduced 10-fold. The importance of position of charge within a dipeptide on substrate binding has also been investigated using dipeptides where the charged amino acid residue is present at either the amino or carboxyl terminus. The results showed that the apparent order of affinity reversed upon extracellular acidification, thus charged residues within the peptide play an important role in substrate binding. The acute regulation of the oligopeptide transporter has been examined by studying the effects of phorbol esters on the transport of a neutral peptide, Gly-Gln. The active ester, PMA, was shown to decrease both the Ka and the Imax. Immunocytochemical studies have confirmed the electrophysiological findings.